DESIGN OF FUEL’S VOLUME MEASUREMENT MONITORING SYSTEM ON INDONESIAN NAVY FUEL TANK “SPBT” BASED ON THE Internet of Things (IoT) - Mochammad Faturrochman; Suprayitno Suprayitno; M Zulkifli; Edy Widodo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
Refueling Stations are places where motorized vehicles can get fuel. The Refueling Station in theTNI is known as the SPBT (TNI Refueling Station) or often referred to as the gas station. SPBT generallyonly provides two types of fuel such as Premium (MT88) and diesel (HSD). This SPBT usually has a tankthat is used to hold fuel oil which will later be used for Dinas vehicles. The development of science,technology creation at this time has penetrated digital technology. Most of the technology used byhumans is completely digital. In this case it is very helpful in various aspects, for example in the industrialsector, many industrial fields have used digital technology due to human limitations and are demanded tobe fast, practical and precise. Of the several applications of digital technology, one that is needed in anindustrial field is a tool to monitor a material that is in a closed container. This technology helps officials tomonitor the amount of fuel from the field without having to open the material container when they want tofind out information about the fuel. As one example is the technology to monitor the condition of fuel oilstorage tanks in the SPBT within the Navy to find out information on the volume of fuel in the tank.Keywords: Kodiklatal SPBT, Internet Of Things (IoT) Fuel Volume Monitoring System.